Japanese encephalitis with Acute respiratory distress syndrome: A rare presentation - Dr. Anil Bapurao Kurane; Dr. Saiprasad Onkareshwar Kavthekar; Dr. Varun Ramchandra Bilagi; Dr. Roma Abhay Chougale (Pediatric Review: International Journal of Pediatric Research, 2018)
A 15 years girl presented with high grade fever, headache, vomiting, loose stools, neck stiffness and positive Kernig’s sign further more developed Shock with ARDS, landed in coma (GCS=3), with changing neurological signs, hemodynamically well managed and serum tested positive for JE virus, who later recovered without any neurological deficit.